A conceptual framework of it security governance and internal controls - Nadianatra Musa (Penerbit Universiti Kebangsaan Malaysia, 2018)
The Board and senior management use internal controls and IT risk governance to ensure that the corporation’s directives such as security policies, standards, procedures, guidelines, administrative rules and practices at all organizational levels are properly chosen and adapted to the organization, implemented and enforced. There were three research problems identified in this paper, lack of involvement of the board and senior management in understanding IS/IT security problems, unbalanced implementation of IS/IT security within the Formal, Technical and Informal components and lack of internal control applications over IS/IT security. This had led to the development of a conceptual framework of IT Security Governance and Internal Controls. Interviews were undertaken with eight Malaysian Publicly Listed Companies to identify the issues that relate to IS/IT Security Governance in Malaysia. The findings reported in the data analysis were consistent with the conceptual framework of IT Security Governance and Internal Controls.